Method for simply and rapidly detecting LDP defect density of silicon single crystal
By applying copper nitrate solution on silicon single crystal samples and performing high-temperature heat treatment, combined with the use of mixed acid solution and preferred corrosion solution, LDP defects appear, and its density is calculated through macro observation, the problems of long detection time and low accuracy in the prior art are solved, and fast and accurate detection of LDP defect density is achieved.
Patent Information
- Application Number
- CN202411945206.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The method for detecting the defect density of single crystals of silicon in the prior art has a long detection time and low accuracy.
By applying copper nitrate solution to the surface of silicon single crystal sample and performing high-temperature heat treatment, the copper ions diffuse, and then using mixed acid solution and preferred corrosion solution to show defects. By macroscopic observation of whether a central aggregation ring or radius ring appears, the LDP defect density is calculated based on the ring width.
It realizes rapid and accurate detection of the defect density of single crystal silicon LDP, avoids errors in artificial microscopic detection, and improves detection efficiency and accuracy.
Smart Images

Figure CN119779789A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor silicon single crystal defect detection, and in particular relates to a method for simply and quickly detecting the LDP defect density of a silicon single crystal. Background Art
[0002] In the field of semiconductor materials, silicon single crystals are the basic materials of integrated circuits, and their quality directly determines the performance and reliability of integrated circuits. However, various defects will occur during the growth and processing of silicon single crystals, among which large dislocation pits (LDPs) are a typical interstitial silicon atom defects, which mainly occur in the I-rich (interstitial atom-rich) region of silicon single crystals.
[0003] The impact of LDP defects on integrated circuits is crucial. It not only reduces the yield of integrated circuits, but also affects the electrical performance and reliability of integrated circuits, thereby increasing production costs and reducing product competitiveness. Therefore, accurate and rapid detection and evaluation of LDP defects are of great significance for improving the quality of silicon single crystals and ensuring the performance of integrated circuits. However, different manufacturers have different requirements for the degree of silicon single crystal LDP defects. The silicon single crystal LDP defect density is an important indicator for judging the degree of silicon single crystal LDP defects. The greater the silicon single crystal LDP defect density, the more serious the silicon single crystal LDP defect, and the smaller the silicon single crystal LDP defect density, the smaller the silicon single crystal LDP defect.
[0004] The traditional method of evaluating LDP defect density requires processing the silicon wafer into a polished wafer state, then performing microscopic inspection through a microscope, and then manually counting the specific number of LDPs to calculate the density. This method takes a long time to detect and the accuracy of manual density counting is low. Summary of the invention
[0005] In view of this, the present invention provides a method for simply and quickly detecting the LDP defect density of a silicon single crystal, so as to solve the technical problems of long detection time and low accuracy in the prior art.
[0006] To achieve the above objectives, this application adopts the following scheme:
[0007] A method for simply and quickly detecting LDP defects in silicon single crystals comprises the following steps:
[0008] S10. Cleaning the silicon single crystal sample to be tested;
[0009] S20. Applying a copper nitrate solution having a copper ion concentration of 700 ppma to 1000 ppma to the surface of the cleaned silicon single crystal sample, and then drying it naturally;
[0010] S30. subjecting the dried silicon single crystal sample to a high temperature heat treatment for a first preset time to diffuse the copper ions on the silicon single crystal sample, wherein the temperature during the high temperature heat treatment is a first preset temperature, and then naturally cooling to room temperature;
[0011] S40. Cleaning the cooled silicon single crystal sample with a mixed acid solution for a second preset time to remove the copper nitrate solution and the oxide film on the surface of the silicon single crystal sample;
[0012] S50. Cleaning the silicon single crystal sample with deionized water to remove the mixed acid solution remaining on the surface of the silicon single crystal sample;
[0013] S60. placing the cleaned silicon single crystal sample in a selective etching solution and subjecting it to selective etching for a third preset time;
[0014] S70. After the preferential etching, the preferential etching liquid on the surface of the silicon single crystal sample is cleaned with deionized water, and the sample is observed. If a central aggregation ring or a radius ring is present on the silicon single crystal sample, the silicon single crystal sample has an LDP defect. If no central aggregation ring or radius ring is present on the silicon single crystal sample, the silicon single crystal sample does not have an LDP defect.
[0015] S80. Measure the ring width of the central aggregation ring or the ring width of the radius ring presented on the silicon single crystal sample, and calculate the LDP defect density according to the ring width. The density of the LDP defect is calculated by the following formula:
[0016] y=0.1131x-1.4485
[0017] Where: y is the LDP defect density and x is the ring width.
[0018] Preferably, in the step S10, the "cleaning the silicon single crystal sample to be tested" includes: using an alkaline cleaning solution to perform alkaline cleaning on the silicon single crystal sample to remove dirt and grease on the surface of the silicon single crystal sample.
[0019] Preferably, the alkaline washing solution is a NaOH solution with a mass concentration of 8% to 10%.
[0020] Preferably, in step S20, the ratio of the mass of the copper nitrate solution applied to the surface of the silicon single crystal sample to the area of the silicon single crystal sample is (2 ml to 3 ml): 7 cm.
[0021] Preferably, in S30, the first preset temperature is 850°C to 950°C.
[0022] Preferably, in S30, the first preset time length is 3 minutes to 5 minutes.
[0023] Preferably, in S40, the second preset time length is 3 minutes to 5 minutes.
[0024] Preferably, in S60, the preferential etching solution is Wright, and the Wright is composed of HF, HAc, CrO3, HNO3, and Cu(NO3)·3H2O with a mass concentration of 49%.
[0025] Preferably, in S60, the third preset time length is 1 minute to 5 minutes.
[0026] Preferably, in S40, the mixed acid solution includes: HF with a mass concentration of 49%, HNO3 with a mass concentration of 70%, CH3OOH with a mass concentration of 99%, and H2O, and the proportions of HF, HNO3, CH3OOH and H2O in the mixed acid solution are (10% to 15%): (20% to 35%): (10% to 20%): (20% to 40%).
[0027] In the above-mentioned method for simply and quickly detecting the LDP defect density of silicon single crystals, a copper nitrate solution is applied to the surface of the cleaned silicon single crystal sample, and a high-temperature heat treatment is performed on it for a first preset time to diffuse the copper ions on the silicon single crystal sample, and a mixed acid solution is used to corrode the cooled silicon single crystal sample for a second preset time to remove the copper nitrate solution and the oxide film on the surface of the silicon single crystal sample, and deionized water is used to wash away the mixed acid solution remaining on the surface of the silicon single crystal sample, and the sample is placed in a preferential etching solution for preferential etching for a third preset time to reveal the defects inside the silicon single crystal sample, and then the preferential etching solution on the surface of the silicon single crystal sample is cleaned with deionized water. The above steps make the defective silicon single crystal sample The surface of the crystal sample presents a clear central aggregation ring or radius ring with regular edges. After the detection, it is only necessary to observe the central aggregation ring or radius ring on the surface of the silicon single crystal through macroscopic observation to determine whether the silicon single crystal sample has LDP defects. If there are LDP defects, the LDP defect density is calculated by the ring width of the central aggregation ring or the radius ring. Compared with the detection method in the prior art, the method does not need to process the silicon single crystal sample into a polished sheet, thereby improving the detection efficiency of the silicon single crystal LDP defect density, and does not need to use a microscope to perform microscopic detection on the silicon single crystal sample processed into a polished sheet, and manually count the specific number of LDPs, thereby avoiding large errors in manual counting, thereby improving the accuracy of silicon single crystal LDP defect density detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of a silicon single crystal sample showing a central aggregation ring in the present invention.
[0029] Figure 2 It is a schematic diagram showing the radius ring of the silicon single crystal sample in the present invention.
[0030] Figure 3 It is a correlation diagram between the ring width and the LDP defect density in the present invention. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present application, the present application will be described more comprehensively below in conjunction with the accompanying drawings. And the preferred implementation of the present application is given. However, the present application can be implemented in many different forms and is not limited to the implementation described herein. On the contrary, the purpose of providing these implementations is to make the disclosure of the present application more thoroughly and comprehensively understood.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0033] A method for simply and quickly detecting LDP defects in silicon single crystals comprises the following steps:
[0034] S10. Clean the silicon single crystal sample to be tested, which is a 1 / 4 slug silicon wafer (12 inches), to remove dirt and oil on the surface to prevent the dirt and oil attached to the surface from affecting the accuracy of the test;
[0035] S20. Apply a copper nitrate solution having a copper ion concentration of 700 ppma to 1000 ppma to the surface of the cleaned silicon single crystal sample, and let it stand for 2 to 4 minutes to allow the copper nitrate solution on the surface of the silicon single crystal sample to dry naturally, and place the silicon single crystal sample with the engraved surface facing upward on a dust-free paper to prevent stains on the surface of the silicon single crystal from being directly placed on the desktop;
[0036] S30. subjecting the dried silicon single crystal sample to a high-temperature heat treatment for a first preset time to diffuse the copper ions on the silicon single crystal sample, wherein the temperature during the high-temperature heat treatment is a first preset temperature, and then naturally cooling to room temperature. Specifically, the dried silicon single crystal sample can be placed on a quartz boat, and when the temperature of the muffle furnace rises to the first preset temperature, the quartz boat is placed in the muffle furnace with a quartz boat fork, and the quartz boat is taken out after the high-temperature heat treatment for a second time;
[0037] S40. Cleaning the cooled silicon single crystal sample with a mixed acid solution for a second preset time to remove the copper nitrate solution and the oxide film on the surface of the silicon single crystal sample;
[0038] S50. Cleaning the silicon single crystal sample with deionized water to remove the mixed acid solution remaining on the surface of the silicon single crystal sample;
[0039] S60. placing the cleaned silicon single crystal sample in a selective etching solution and subjecting it to selective etching for a third preset time;
[0040] S70. After the preferential etching, the preferential etching liquid on the surface of the silicon single crystal sample is cleaned with deionized water, and the sample is observed (by naked eyes for macroscopic observation). If a central aggregation ring or a radius ring is present on the silicon single crystal sample, the silicon single crystal sample has LDP defects. If the silicon single crystal sample does not have such a central aggregation ring or a radius ring, the silicon single crystal sample has LDP defects. Figure 1 and Figure 2 If the central aggregation ring or radius ring shown in , the silicon single crystal sample does not have LDP defects;
[0041] S80. Measure the ring width of the central aggregation ring or the ring width of the radius ring presented on the silicon single crystal sample, and calculate the LDP defect density according to the ring width. The density of the LDP defect is calculated by the following formula:
[0042] y=0.1131x-1.4485
[0043] Wherein: y is the LDP defect density, x is the ring width, and the 0.1131 and -1.4485 are coefficients calibrated through multiple experiments. Therefore, the LDP defect density calculated using this formula is very accurate.
[0044] In the above-mentioned method for simply and quickly detecting the LDP defect density of silicon single crystals, a copper nitrate solution is applied to the surface of the cleaned silicon single crystal sample, and a high-temperature heat treatment is performed on it for a first preset time to diffuse the copper ions on the silicon single crystal sample, and a mixed acid solution is used to corrode the cooled silicon single crystal sample for a second preset time to remove the copper nitrate solution and the oxide film on the surface of the silicon single crystal sample, and deionized water is used to wash away the mixed acid solution remaining on the surface of the silicon single crystal sample, and the sample is placed in a preferential etching solution for preferential etching for a third preset time to reveal the defects inside the silicon single crystal sample, and then deionized water is used to corrode the surface of the silicon single crystal sample. The silicon single crystal sample is cleaned with the preferential etching solution, and its surface is macroscopically observed to see whether a central aggregation ring or a radius ring is present, so as to determine whether it has LDP defects. If it has LDP defects, the LDP defect density is calculated by the ring width of the central aggregation ring or the radius ring. Compared with the detection method in the prior art, the method does not need to process the silicon single crystal sample into a polished sheet, thereby improving the detection efficiency of the silicon single crystal LDP defect density, and does not need to use a microscope to perform microscopic detection on the silicon single crystal sample processed into a polished sheet, and manually count the specific number of LDPs, thereby avoiding large errors in manual counting, thereby improving the accuracy of silicon single crystal LDP defect density detection.
[0045] Among them, in said S10, said "cleaning the silicon single crystal sample to be tested" includes: using alkaline cleaning solution to perform alkaline cleaning on the silicon single crystal sample to remove dirt and grease on the surface of the silicon single crystal sample.
[0046] Preferably, the alkaline washing solution is a NaOH solution with a mass concentration of 8% to 10%.
[0047] Specifically, in S20, if the amount of the copper nitrate solution applied is too little, the above-mentioned effect cannot be achieved, and if the amount of the copper nitrate solution applied is too much, resources will be wasted. Therefore, the ratio of the mass of the copper nitrate solution applied to the surface of the silicon single crystal sample to the area of the silicon single crystal sample is 2ml to 3ml:7cm to achieve better effect.
[0048] Specifically, in S30, the first preset temperature is 850°C to 950°C; the first preset time is 3min to 5min; in S40, the second preset time is 3min to 5min; in S60, the third preset time is 1min to 5min.
[0049] Among them, in the S60, the preferred etching solution is wright, and the wright is prepared according to the national standard ratio. The wright is composed of HF, HAc, CrO3, HNO3, and Cu(NO3)·3H2O with a mass concentration of 49%.
[0050] In S40, the mixed acid solution includes: HF with a mass concentration of 49%, HNO3 with a mass concentration of 70%, CH3OOH with a mass concentration of 99%, and H2O. The proportions of HF, HNO3, CH3OOH and H2O in the mixed acid solution are (10% to 15%): (20% to 35%): (10% to 20%): (20% to 40%).
[0051] The following specific experimental examples are used to further illustrate the technical solutions and technical effects of the present invention. It should be noted that the following experimental examples are only for further explaining the present invention and do not limit the technical solutions of the present invention.
[0052] Experimental Example 1
[0053] Step 1: Take a 12-inch sample with LDP defect density measured by a traditional method and cleave it into four quarters of single crystal silicon samples, take one of them for testing, use a NaOH solution with a mass concentration of 8% as an alkaline cleaning solution to clean the single crystal silicon sample, and then use deionized water to clean the NaOH solution on the surface of the single crystal silicon sample;
[0054] Step 2: Place the cleaned single crystal silicon sample with the engraved surface facing upward on a dust-free paper, apply a copper nitrate solution with a copper ion concentration of 700ppma to 1000ppma to the surface of the silicon single crystal sample, the ratio of the mass of the copper nitrate solution to the area of the silicon single crystal sample is 2ml:7cm, and let it stand for 2min to dry;
[0055] Step 3, placing the single crystal silicon sample on a quartz boat, and when the temperature of the muffle furnace rises to 900° C., using a quartz boat fork to place the quartz boat in the muffle furnace, taking out the quartz boat after heat treatment for 4 minutes, and allowing the single crystal silicon sample to cool naturally to room temperature;
[0056] Step 4: Use a mixed acid solution to clean the cooled silicon single crystal sample for 2 minutes to remove the copper nitrate solution and the oxide film on the surface of the silicon single crystal sample, wherein the mixed acid solution comprises: HF with a mass concentration of 49%, HNO3 with a mass concentration of 70%, CH3OOH with a mass concentration of 99%, and H2O, wherein the proportions of HF, HNO3, CH3OOH, and H2O in the mixed acid solution are 12%:32%:18%:38%;
[0057] Step 5: Cleaning the silicon single crystal sample with deionized water to remove the mixed acid solution remaining on the surface of the silicon single crystal sample;
[0058] Step 6: placing the cleaned silicon single crystal sample in a selective etching solution for selective etching for 4 minutes to reveal defects in the silicon single crystal sample;
[0059] Step 7: Clean the silicon single crystal sample with deionized water, blow off the water droplets on the surface with a water gun, and then send it to the darkroom of the inspection room for inspection. The silicon single crystal sample shows a central aggregation ring, indicating that the silicon single crystal sample has LDP defects;
[0060] Step 8: Measure the width of the central aggregation ring on the silicon single crystal sample, where the width is 40 mm, and calculate the LDP defect density according to the following formula:
[0061] y=0.1131x-1.4485
[0062] Where: y is the LDP defect density, x is the ring width
[0063] The calculation results are as follows Figure 3As shown, it is explained that the method provided in this embodiment can not only judge the presence or absence of LDP defects through macroscopic analysis with a judgment accuracy of 100%, but also calculate the LDP defect density through the ring width. Since this embodiment uses a truncated silicon single crystal rough slice as a silicon single crystal sample with a poor surface state, if the traditional method is used for detection, the detection result obtained will be affected by the judgment due to the interference of surface damage, so the judgment accuracy is not high. The method provided in this embodiment uses a copper pendant and then selectively corrodes to observe the defects in the silicon wafer body, which will not affect the judgment result due to the surface state. There is no need to use a microscope to observe microscopically and then artificially count the specific number of LDPs to calculate the LDP defect density. A clear pattern can be observed only through the macroscopic analysis, and the LDP defect density is calculated through the ring width of the pattern, which improves the detection efficiency and accuracy.
[0064] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.
Claims
1. A method for simply and quickly detecting the LDP defect density of a silicon single crystal, characterized in that: The following steps are involved: S10. Cleaning the silicon single crystal sample to be tested; S20. Applying a copper nitrate solution having a copper ion concentration of 700 ppma to 1000 ppma to the surface of the cleaned silicon single crystal sample, and then drying it naturally; S30. subjecting the dried silicon single crystal sample to a high temperature heat treatment for a first preset time to diffuse the copper ions on the silicon single crystal sample, wherein the temperature during the high temperature heat treatment is a first preset temperature, and then naturally cooling to room temperature; S40. Cleaning the cooled silicon single crystal sample with a mixed acid solution for a second preset time to remove the copper nitrate solution and the oxide film on the surface of the silicon single crystal sample; S50. Cleaning the silicon single crystal sample with deionized water to remove the mixed acid solution remaining on the surface of the silicon single crystal sample; S60. Placing the cleaned silicon single crystal sample in a preferential etching solution for preferential etching for a third preset time; S70. After the preferential etching, use deionized water to clean the preferential etching solution on the surface of the silicon single crystal sample, and observe it. If a central aggregation ring or a radius ring is present on the silicon single crystal sample, the silicon single crystal sample has an LDP defect. If no central aggregation ring or radius ring is present on the silicon single crystal sample, the silicon single crystal sample does not have an LDP defect; S80. Measure the ring width of the central aggregation ring or the ring width of the radius ring presented on the silicon single crystal sample, and calculate the LDP defect density according to the ring width. The density of the LDP defect is calculated by the following formula: y=0.1131x-1.4485 Where: y is the LDP defect density and x is the ring width.
2. The method for simply and quickly detecting the LDP defect density of a silicon single crystal according to claim 1, characterized in that: In the S10, the "cleaning the silicon single crystal sample to be tested" includes: using an alkaline cleaning solution to perform alkaline cleaning on the silicon single crystal sample to remove dirt and grease on the surface of the silicon single crystal sample.
3. The method for simply and quickly detecting the LDP defect density of a silicon single crystal according to claim 2, characterized in that: The alkaline washing liquid is a NaOH solution with a mass concentration of 8% to 10%.
4. The method for simply and quickly detecting the LDP defect density of a silicon single crystal according to claim 1, characterized in that: In S20, the ratio of the mass of the copper nitrate solution applied to the surface of the silicon single crystal sample to the area of the silicon single crystal sample is (2 ml to 3 ml): 7 cm.
5. The method for simply and quickly detecting the LDP defect density of a silicon single crystal according to claim 1, characterized in that: In the S30, the first preset temperature is 850°C to 950°C.
6. The method for simply and quickly detecting the LDP defect density of a silicon single crystal according to claim 1, characterized in that: In S30, the first preset time length is 3 minutes to 5 minutes.
7. The method for simply and quickly detecting the LDP defect density of a silicon single crystal according to claim 1, characterized in that: In S40, the second preset time length is 3 minutes to 5 minutes.
8. The method for simply and quickly detecting the LDP defect density of a silicon single crystal according to claim 1, characterized in that: In the S60, the preferential etching solution is wright, and the wright is composed of HF, HAc, CrO3, HNO3, and Cu(NO3)·3H2O.
9. The method for simply and quickly detecting the LDP defect density of a silicon single crystal according to claim 1, characterized in that: In S60, the third preset time length is 1 minute to 5 minutes.
10. The method for simply and quickly detecting the LDP defect density of a silicon single crystal according to claim 1, characterized in that: In S40, the mixed acid solution includes: HF with a mass concentration of 49%, HNO3 with a mass concentration of 70%, CH3OOH with a mass concentration of 99%, and H2O. The proportions of HF, HNO3, CH3OOH and H2O in the mixed acid solution are (10% to 15%): (20% to 35%): (10% to 20%): (20% to 40%).
Citation Information
Patent Citations
Etching solution for dislocation display of monocrystal germanium wafer deflecting to crystal orientation [111] and etching method
CN104862702A
Method for detecting defects in semiconductor material
CN113394126A
Method and system for detecting defects in silicon single crystal rod
CN115931863A
Method for characterizing silicon single crystal defects
CN117250205A
Method for detecting axial dislocation defect of heavily boron-doped silicon single crystal
CN117607150A